2014
DOI: 10.3892/mmr.2014.2290
|View full text |Cite
|
Sign up to set email alerts
|

Germacrone inhibits the proliferation of glioma cells by promoting apoptosis and inducing cell cycle arrest

Abstract: Germacrone is one of the major bioactive components of the traditional Chinese Medicinal plant Curcuma aromatica Salisb. and has been shown to possess anti‑tumor properties. In the present study, the anti‑proliferative effect of germacrone on human glioma cells and the molecular mechanism underlying its cytotoxicity were investigated. Treatment of the U87 and U251 human glioma cell lines with germacrone inhibited the cell proliferation in a dose‑ and time‑dependent manner as assessed by MTT assay, while signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Liu et al observed that GM‐induced apoptosis in HepG2 cells via suppression of the JAK2/STAT3 signaling pathway. In another study, it was shown that GM inhibited the proliferation of glioma cells by elevating apoptosis and promoting cell cycle arrest . These two studies show a contrary effect from what we observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Liu et al observed that GM‐induced apoptosis in HepG2 cells via suppression of the JAK2/STAT3 signaling pathway. In another study, it was shown that GM inhibited the proliferation of glioma cells by elevating apoptosis and promoting cell cycle arrest . These two studies show a contrary effect from what we observed.…”
Section: Discussionsupporting
confidence: 92%
“…11 GM exerted a remarkable protective effect on acute liver injury in mice. 12,13 Liu et al 14 showed that treatment with GM suppressed cell proliferation.…”
mentioning
confidence: 99%
“…Biological activities Curcuma aeruginosa Antimicrobial [164] , cytotoxicity [152] ; antinociceptive, antipyretic [13] ; uterine relaxant [74] ; antioxidant [165] ; inhibition of nitric oxide production [166] ; and anti-inflammatory [153] Curcuma amada Antifungal and insecticidal [79] ; CNS depressant and analgesic [16,167] ; antiulcer [168] ; anti-tubercular [135] ; antioxidant, antimicrobial, cytotoxic and antiplatelet [20] ; anti-inflammatory [169] ; anticancer [170] ; and larvicidal [171] Curcuma angustifolia Antimicrobial, antiulcerogenic [172,173] ; antioxidant [155] ; antifungal and antibacterial [129] Curcuma aromatica Hypoglycemic [172] ; anti-Alzheimer [173] ; antioxidant [2] ; cytotoxicity [174] ; insecticidal [175] ; antiinflammatory [169] ; antibacterial [11] ; inhibition of nitric oxide production [176] ; antiproliferative [177] ; and gastroprotective [21] Curcuma australasica Inhibition of nitric oxide and prostaglandin production, anti-inflammatory, and cytotoxic [115] Curcuma caesia Smooth muscle relaxant [178] ; anxiolytic, CNS depressant and neuropharmacological [179,180] ; antimicrobial [151] ; antiulcerogenic [181] ; antitumor and antioxidant [116] ; anticancer [182] ; antihepatotoxicity and nephrotoxicity [...…”
Section: Plant Speciesmentioning
confidence: 99%
“…In particular, the germacrone and oseltamivir combination has a synergistic effect on the inhibition of influenza virus. On the other hand, there are no reports on potential antitumor activity in vivo [33]. The main possible reasons for this phenomenon are: (1) germacrone is mainly extracted and isolated from plants with relatively low yield, therefore the purchase price is high, while the dosage for animal experiments is large; (2) the water solubility of germacrone is relatively poor; and (3) the lack of an antitumor and antivirus mechanism.…”
Section: Discussionmentioning
confidence: 99%